Legal Frameworks, Transparency, and Oversight: Ensuring Public Confidence in Online Donation Platforms - Noor, Afif; Afif, Aqila-Syarief Muhammad; Azmi, Muhammad Fazli; Dwi Wulandari (Indonesian State Law Review, 2025)
The proliferation of digital technology has markedly accelerated the expansion of online donation platforms in Indonesia. Concurrently, with the rise in public engagement in online philanthropic endeavours, several challenges have surfaced, including the potential for fund misuse, lack of transparency, and inadequate oversight mechanisms. This study examines how legal frameworks, transparency, and oversight can collaboratively safeguard and enhance public trust in online donation systems. The methodology employed is a qualitative study with a normative approach involving the analysis of existing regulations, literature reviews, and case studies related to digital donation mismanagement. The findings reveal the lack of comprehensive legal regulations governing online donations, accountability mechanisms among platform providers, and limited public access to financial information. The study further underscores the importance of implementing principles of good governance, utilizing transparency-enhancing technologies such as blockchain, and strengthening independent reporting and auditing systems to prevent fund misappropriation. In conclusion, public trust in online donation systems can only be cultivated through reinforced legal frameworks, increased operational transparency, and oversight involving multiple stakeholders. The study recommends formulating national regulations addressing digital donations, active involvement of independent supervisory institutions, and continuous public education to ensure that the public is informed and aware, thereby establishing a secure, accountable, and sustainable online donation ecosystem.